Advanced masking agent for leather tanning from stepwise degradation and oxidation of cellulose. Issue 11 (12th May 2021) - Jiang, Zhicheng; Xu, Shuguang; Ding, Wei; Gao, Mi; Fan, Jiajun; Hu, Changwei; Shi, Bi; Clark, James H.
Abstract : An oligosaccharide-based masking agent for Cr-free metal tanning was produced from cellulose via a stepwise degradation and oxidation process. Abstract : An oligosaccharide-based masking agent suitable for chrome-free metal tanning was produced from cellulose via a stepwise degradation and oxidation process. Firstly, an AlCl3 -NaCl-H2 O/γ-valerolactone (GVL) biphasic solvent system was established for cellulose conversion (87.6%), which allowed in situ separation of the oligosaccharides and valuable small molecules into the two phases. Then, a H2 O2 oxidation process enabled further degradation of the oligosaccharides and introduced –CHO/–COOH groups. This process strengthened the surface charge of the oligosaccharides, enhancing their coordination ability with metal ions. The post-oxidized fraction, together with added Zr species, exhibited satisfactory tanning performance, with a shrinkage temperature of 85.2 °C for the tanned leather. Al/Zr species could spontaneously coordinate with O atoms of OC(2) in the carboxylic group of post-oxidized oligosaccharides, which promoted the penetration of Al/Zr species into the leather matrix for efficient crosslinking reactions.